EFEK KEKURANGAN ENERGI PROTEIN TERHADAP GAMBARAN HISTOLOGI DUODENUM TIKUS PUTIH (Rattus norvegicus) GALUR Sprague-Dawley - ., Jovi Pardomuan Siagian (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2015)
Background Childhood malnutrition is a problem in developing countries, andpathological changes in digestive organ such as duodenum might play a part in theprogression of the disease. An animal model to study the microscopic features ofduodenum could prove important in evaluating the pathophysiology of the condition.Methods This research is an experimental using a post-test only with control groupsdesign. 30 three week-old rats were given access to either an 8 g/100 gBW/day diet(CONTROL, n=15) or a 4 g/100 gBW/day diet (MALNOURISHED, n=15) for 21days. Every 7 days, five rats from each group were euthanized and their duodenumswere collected for histological samples. Histological samples were made from crosssectionsof duodenums and stained with haematoxylin-eosin. Villous height, cryptsdepth and mucosal thickness were recorded from these histological samples. ResultMalnourished rats give lower numbers across all histological parameters comparedto their corresponding counterparts in the control group. Furthermore, theparameters in malnourished rats that were euthanized after 14 days are lower thanthose that were euthanized after 7 days. However, malnourished rats that wereeuthanized after 21 days give higher numbers in all parameters than those that wereeuthanized after 14 days. Conclusion Duodenal morphologies are compromisedduring malnutrition but undergo adaptation mechanism to compensate for the lowintake of protein and calorie. This rat model is relevant for a better understanding ofthe pathophysiology of malnutrition.Keywords: Protein-energy malnutrition, duodenum, villous height, crypts depth,mucosal thickness